1991
DOI: 10.1093/ageing/20.2.107
|View full text |Cite
|
Sign up to set email alerts
|

The Increase in Body Temperature of Elderly Patients in the First Twenty-four Hours Following Admission to Hospital

Abstract: In 76 unselected patients aged 70 years or over, the mean increase in rectal temperature in the 24 hours following admission to hospital was 0.4 degrees C. In those who did not receive antibiotics on admission, the mean increase in rectal temperature was 0.6 degrees C, with increases of up to 2.3 degrees C recorded. There were no significant changes in C-reactive protein, white cell count or erythrocyte sedimentation rate over that period, suggesting that the changes were due to passive warming rather than to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Darwosky et al found that in patients aged 70 y and older sublingual temperature readings detect about one-third of fevers and that rectal temperature measurement will detect fever in up to 86% of infected patients. 26,27 In the study of Hernandez et al, who reported 6.3% absence of fever, the definition of fever was rectal or oral temperature above 37.8, while in other studies higher temperatures were considered fever. 14 …”
Section: Body Temperaturementioning
confidence: 99%
“…Darwosky et al found that in patients aged 70 y and older sublingual temperature readings detect about one-third of fevers and that rectal temperature measurement will detect fever in up to 86% of infected patients. 26,27 In the study of Hernandez et al, who reported 6.3% absence of fever, the definition of fever was rectal or oral temperature above 37.8, while in other studies higher temperatures were considered fever. 14 …”
Section: Body Temperaturementioning
confidence: 99%
“…Though enshrined as an example of atypical presentation in old age, this observation is based on uncontrolled clinical observations in ill-defined patient populations. 40 Presumably these patients were either at a very early stage of their infection or were unable to increase heat production or prevent heat loss sufficient to raise body temperature until they were in an environment that approximated to their thermoneutral zone. axilla or buccal cavity, both sites of heat loss) and it is the core temperature that is upregulated in fever.…”
Section: Clinical Features Of Urinary Infectionmentioning
confidence: 99%